Champions [videorecording (DVD)] - Rizzo, Mark; Harrelson, Woody; Olson, Kaitlin; Cook, Matt, 1984-; Hudson, Ernie; Marin, Cheech; Franti, Michael, 1966-; Miles, C. Kim (Universal Studios, 2023)
A former minor-league basketball coach is ordered by the court to manage a team of players with disabilities. He soon realizes that despite his doubts, together, this team can go further than they ever imagined.